1998
DOI: 10.1590/s0100-879x1998001100014
|View full text |Cite
|
Sign up to set email alerts
|

Karyological, biochemical, and physiological aspects of Callophysus macropterus (Siluriformes, Pimelodidae) from the Solimões and Negro Rivers (Central Amazon)

Abstract: Karyological characteristics, i.e., diploid number, chromosome morphology and nucleolus organizer regions (NORs), biochemical characteristics, i.e., electrophoretic analysis of blood hemoglobin and the tissue enzymes lactate dehydrogenase (LDH), malate dehydrogenase (MDH), alcohol dehydrogenase (ADH), and phosphoglucose isomerase (PGI), and physiological characteristics, i.e., relative concentration of hemoglobin and intraerythrocytic concentrations of organic phosphates were analyzed for the species Callophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This large chromosome, a clear cytogenetic marker, also occurs in the karyotype of Calophysus macropterus (Ramirez-Gil et al 1998) and Pinirampus pirinampu studied by Swarça et al (1999) and Vasconcelos and Martins-Santos (2000), as a synapomorphic feature of the Calophysus group. Thus, a chromosome fusion could have occurred subsequently to the differentiation of the common ancestor that originated this fish group.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This large chromosome, a clear cytogenetic marker, also occurs in the karyotype of Calophysus macropterus (Ramirez-Gil et al 1998) and Pinirampus pirinampu studied by Swarça et al (1999) and Vasconcelos and Martins-Santos (2000), as a synapomorphic feature of the Calophysus group. Thus, a chromosome fusion could have occurred subsequently to the differentiation of the common ancestor that originated this fish group.…”
Section: Discussionmentioning
confidence: 73%
“…Further cytogenetic studies carried out in Siluriformes support the Le Grande hypothesis, whereby almost all species described showed diploid numbers ranging from 2nϭ54 to 2nϭ58 (Oliveira and Gosztonyi 2000). Cytogenetic studies of Pinirampus pirinampu (Swarça et al 1999, Vasconcelos andMartins-Santos 2000) and Calophysus macropterus (Ramirez-Gil et al 1998) showed the same diploid number of 2nϭ50. The available data on this group are summarized in Table 1.…”
mentioning
confidence: 76%
“…1a). In a review on the cytogenetic studies of 27 species of the family Pimelodidae by Swarça et al (2007), 23 had a diploid number of 56 chromosomes, three had 2n = 50 chromosomes: Pinirampus pirinampu (Spix & Agassiz, 1829) (Swarça et al, 1999;Vasconcelos & Martins-Santos, 2000), Luciopimelodus pati (Valenciennes, 1835) (Sánchez, 2006), and Calophysus macropterus (Liechtenstein, 1819) (Ramirez-Gil et al, 1998), and one had 2n = 54 chromosomes: Pimelodus fur (Lütken, 1874) (Garcia & Moreira-Filho, 2005).…”
mentioning
confidence: 99%
“…piperatus (Vissotto et al 2001), Rhamdella microcephala (Fonseca et al 2003), and 2nϭ58 in Rhamdia quelen (Hochberg andErdtmann 1988, Fenocchio andBertollo 1990), Pimelodella kronei and Pimelodella transitoria (Almeida-Toledo et al 1992), Imparfinis mirini (Vissotto et al 1997), Cetopsorhamdia iheringi (Vissotto et al 1999a) and Imparfinis piperatus (Vissotto et al 2001). Among Pimelodidae, 2nϭ50 chromosomes were found in Calophysus macropterus (Ramirez-Gil et al 1998), Pirinampus pirinampu (Swarça et al 1999), and 2nϭ56 in Pseudoplatystoma fasciatum and P. tigrinum (Fenocchio and Bertollo 1992), Sorubim lima (Fenocchio and Bertollo 1992), in Bergiaria westermanni (Dias and Foresti, 1993), Pimelodus maculatus (Dias and Foresti 1993), P. argenteus and P. mysteriosus (Souza et al 2003a Pseudoplatystoma corruscans (Martins-Santos et al 1996), Hemisorubim platyrhynchos (MartinsSantos et al 1996), Zungaro zungaro (Martins-Santos et al 1996), Iheringichthys labrosus (Vissotto et al 1999b), and Steindachneridion sp. (Swarça et al 2003b).…”
Section: Resultsmentioning
confidence: 99%